The growth of Cryptococcus gattii MATα and MATa strains is affected by the chemical composition of their woody debris substrate. (October 2020) - Vreulink, Jo-Marie; Boekhout, Teun; Vismer, Hester; Botha, Alfred
Abstract: The dominance of MAT α among cryptococcal strains has been ascribed to MAT a strains being more sensitive to certain environmental factors; however no study has attempted to identify these factors. During the present study we determined whether the chemical composition of woody debris may influence the occurrence of Cryptococcus gattii MAT a . We observed a positive correlation between the numbers of C. gattii MAT a and the ammonium-nitrogen (NH4 –N) concentration in woody debris samples. Subsequent growth studies conducted in woody debris microcosms indicated that this positive correlation is likely not due to additional NH4 Cl improving the growth of selected MAT a strains. Instead, it might be due to the MAT a strains competing better with the MAT α strains in the presence of a high NH4 Cl concentration compared to a low NH4 Cl concentration. This exploratory study paves the way for future studies focused on the interactions of MAT a and MAT α strains with environmental factors. Highlights: C. gattii MAT a numbers correlated positively with the NH4 –N content of woody debris. MAT a strains were less susceptible than MAT α strains to NH4 Cl growth inhibition. MAT a strains had a fitness advantage over MAT α strains at high NH4 –N concentrations.